2013
DOI: 10.1126/science.1240487
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Persistence of College Students in STEM

Abstract: An evidence-based framework offers a guide for efforts to increase student persistence in STEM majors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

21
622
4
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 634 publications
(651 citation statements)
references
References 28 publications
21
622
4
4
Order By: Relevance
“…Furthermore, research indicates that collaboration increases learning, and it is postulated that it does this by increasing skills such as problem solving, data analysis, and metacognition (i.e. learning about learning, as I discovered in my study group as an undergraduate) [14,[16][17][18][19][20].Several studies across Science, Technology, Engineering, and Math (STEM) literature indicate that team-based active learning approaches, not lecture-based learning, improve the performance of under-represented groups to a greater extent than lecture-based learning [18,21,22]. In introductory biology courses, Haak et al found that incorporating even a moderate number of active-learning activities increased exam performance as compared to lecture alone, for all students, including under-represented groups.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, research indicates that collaboration increases learning, and it is postulated that it does this by increasing skills such as problem solving, data analysis, and metacognition (i.e. learning about learning, as I discovered in my study group as an undergraduate) [14,[16][17][18][19][20].Several studies across Science, Technology, Engineering, and Math (STEM) literature indicate that team-based active learning approaches, not lecture-based learning, improve the performance of under-represented groups to a greater extent than lecture-based learning [18,21,22]. In introductory biology courses, Haak et al found that incorporating even a moderate number of active-learning activities increased exam performance as compared to lecture alone, for all students, including under-represented groups.…”
mentioning
confidence: 99%
“…Furthermore, research indicates that collaboration increases learning, and it is postulated that it does this by increasing skills such as problem solving, data analysis, and metacognition (i.e. learning about learning, as I discovered in my study group as an undergraduate) [14,[16][17][18][19][20].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Undergraduate instructors continue to struggle to engage, effectively teach, and retain postsecondary students, both generally and particularly among women and students of color (3,4). Federal analyses suggest that a 10% increase in retention of undergraduate STEM students could address anticipated STEM workforce shortfalls (5).…”
mentioning
confidence: 99%
“…While efforts to recruit pre-college students to STEM may increase initial interest, many students choose engineering to "change the world" and become disillusioned or lose interest 2 when faced with learning foundational concepts, which are presented without connecting the use of concepts to real-world problems. Currently, less than half of the three million students entering higher education to pursue a STEM field persist to earn a STEM degree 3 . The drop-out rate from STEM is even more prominent in minorities and women 4 ; however, participating in undergraduate research and developing a strong peer network has been shown to increase persistence 5,6,7,8,9 .…”
Section: Implementing a Challenge-inspired Undergraduate Experience Imentioning
confidence: 99%